Colour importance driven half-toning - Guerrero, Roberto A. (2002)
Importance driven half-toning (IDH) presents a method for reduced resource rendering of gray scale images. This approach uses an image pyramid to distribute drawing primitives to different areas of the image based on an importance function. The original paper showed how a wide variety of effects can be achieved using a combination of importance functions and drawing primitives. In this paper we show that by storing multiple pyramid representations of the image we can use different geometric primitives in different areas of the image. The application of IDH to colour is then explored. We show that each of the red, green, and blue bands of the image can be used as bases for IDH. We show some images that are obtained in this manner. Finally we introduce a drawing mode based on a teaching drawing style (Esgrafiado with black ink) where a black layer is scratched off a coloured background. The resulting system provides the artist with a large number of parameters with which to render stylized images. We conclude the paper with some examples of our technique being applied to standard images.